The design of a speech delay screening mobile application for Malaysian parents - Mohammed, Siti Asma; Azahari, Nur Faizah; W. A. Sayuti, Wan Nur Shahirah (IIUM Press, International Islamic University Malaysia, 2019)
Some children may face some developmental problems in one or more areas of their developmental milestones. One of them is speech delay. To date, a screening tool for speech delay early detection among children is still lacking, especially in Malaysia. Parents do not know where to refer and which organisation can help them especially for first-time parents. The objective of this paper is twofold. First, this paper analyses existing screening system or application for speech delay in children. Second, this paper proposes a mobile application designed for Malaysian parents to help them detect speech delay in their children. A qualitative expert review was used to design and build the application. The screening application proposed is for early detection and to urge parents to seek for early intervention through appropriate assessments. In conclusion, early detection in speech delay is critically important to increase the chances for improving speech and communication skills. Thus, a speech delay screening tool is needed for parents to seek proper treatment for their children.